2019
DOI: 10.1016/j.ijantimicag.2019.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Long-term data on the efficacy and tolerability of lamivudine plus dolutegravir as a switch strategy in a multi-centre cohort of HIV-1-infected, virologically suppressed patients

Abstract: Long term data on the efficacy and tolerability of lamivudine plus dolutegravir as a switch strategy in a multicenter cohort of HIV1-infected, virologically suppressed patients,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 28 publications
6
59
1
Order By: Relevance
“…Among 556 virologic suppressed PLHIV who switched from a triple or dual regimen (3TC plus boosted PI) to dual ART with DTG and 3TC, 12 patients experienced virologic failure. However, none developed resistance mutations to DTG or 3TC [98]. PLHIV receiving dual ART with RAL plus DRV/r had a high rate (29.5%) of INSTI resistance at virologic failure [97].…”
Section: Evolution Of Hiv Drug Resistancementioning
confidence: 96%
See 1 more Smart Citation
“…Among 556 virologic suppressed PLHIV who switched from a triple or dual regimen (3TC plus boosted PI) to dual ART with DTG and 3TC, 12 patients experienced virologic failure. However, none developed resistance mutations to DTG or 3TC [98]. PLHIV receiving dual ART with RAL plus DRV/r had a high rate (29.5%) of INSTI resistance at virologic failure [97].…”
Section: Evolution Of Hiv Drug Resistancementioning
confidence: 96%
“…In recent years, ART regimens with two ARVs (3TC plus DTG or darunavir/ritonavir (DRV/r), DTG plus rilpivirine (RPV), or DTG plus DRV/r) have been introduced into clinical practice following studies that have shown them to be effective in achieving virologic suppression in treatment-naive adults [90,96,97] and/or maintaining virologic suppression in treatment-experienced adults [98][99][100][101][102][103], with no evidence of the emergence of HIVDR mutations to either of the ARVs used. Studies have shown that dual ART regimens are noninferior to standard triple ARV regimens, and provide the opportunity to reduce adverse effects of ARVs and simplify ART regimens [90, 97-100, 104, 105].…”
Section: Evolution Of Hiv Drug Resistancementioning
confidence: 99%
“…It is a software architecture pattern that separates the three modules of view, controller, and model. e advantage of this design is that system developers and system designers can perform their maintenance [25,26]. erefore, it improves the reuse rate of system code and also improves the scalability of system applications.…”
Section: Mvc Modelmentioning
confidence: 99%
“…Since a potential interaction between time of virological suppression at baseline and RAMs has been previously suggested [ 6 , 7 ], a sensitivity analysis was performed to estimate the effect of M184V/I with and without TAMs in the subgroups of patients with ≤7 and >7 years of virological suppression (median value in our population). Whereas in the group with longer time of virological control no association between RAMs and outcome was detected, patients with shorter duration of virological suppression had a higher risk of VF when M184V/I and TAMs were simultaneously present (compared with absence of RAMs; aHR, 11.56; 95% CI, 2.22–60.08; P = .004), but not when M184V/I was present without TAMs (compared with absence of RAMs; aHR, 4.90; 95% CI, 0.58–41.79; P = .146).…”
Section: Resultsmentioning
confidence: 99%
“…However, long-term follow-up data about the incidence and predictors of virological failure (VF) are still lacking, with some observational reports suggesting worse virological outcomes for patients starting the DT with a shorter time of virological suppression and the presence of M184V/I at historical genotype [ 7 , 8 ]. Although M184V/I is well recognized as the key resistance mutation for 3TC, thymidine analog-associated mutations (TAMs) variably decrease susceptibility to all nucleoside reverse-transcriptase inhibitors (NRTIs), including 3TC [ 9 ].…”
mentioning
confidence: 99%